Intergenerational class mobility in Europe: a new account - Bukodi, E; Paskov, M; Nolan, B (Oxford University Press, 2019)
Comparative research into intergenerational social mobility has been typically restricted to a relatively small number of countries. The aim of this paper is to widen the perspective, and to provide an up-to-date account of rates of intergenerational class mobility across 30 European countries, using a newly-constructed comparative data-set based on the European Social Survey. Absolute mobility rates are found to vary quite widely with national differences in the extent and pattern of class structural change. As regards relative rates, countries are best seen as falling into groups within comparatively high and low fluidity sets, within which groups a high degree of cross-national commonality prevails. Further results indicate that country differences in relative rates play only a very limited part in accounting for country differences in absolute rates, confirming that the latter are primarily determined by class structural change. Based on our findings, we suggest a restatement of the FJH-hypothesis to the effect that in societies with a capitalist market economy, a nuclear family system and a liberal-democratic polity, a limit exists to the extent to which relative rates of class mobility can be equalized, which countries may move closer to or, in the case of post-socialist societies, recede from.